Transmission electron microscopy of the induced damage by argon implantation in (111) HgCdTe at room temperature - Aguirre, Myriam H. (2002)
HgCdTe (MCT) is an important semiconductor material used for infrared photovoltaic detectors. Although ion implantation is a widely used technique in the manufacture of devices based on MCT to obtain n/p junctions, a detailed understanding of the n-type behavior of the unannealed damage region has not yet been established. In this work, n/p junctions were formed by Ar++ implantation on MCT (111) grown by the isothermal vapor phase epitaxy method. Structural damage after implantation for different implantation doses (10 13, 1014, 1015Ar++/cm2) was evaluated by transmission electron microscopy. At high doses, damage distribution exhibits a double region of defects. These were mainly vacancy dislocation loops and lines in the first region, whereas the second zone exhibited small dislocation loops. The observed n-type behavior after implantation was attributed to the generation and diffusion of Hg from the damaged region.